Treatment of Unconsummated Marriage in Psychogenic Erectile Dysfunction among Iranian Couples - Foroutan, Seyed Kazem; Jadid-Milani, Maryam; Lashani, Zeynab; Khayyamfar, Feraidoon (Urology Journal, 2026)
Purpose: Sexual dysfunction associated with psychological reasons is one of the factors impacting unfulfilled marriages. There are limited data on treatment outcomes in this context. The aim of this study was determining the treatment of unconsummated marriage in psychogenic erectile dysfunction in Iranian Couples. Materials and Methods: A total of 66 cases were selected from individuals referred to the Family Health Clinic (from 2006 to 2019), who had unconsummated marriages and experienced psychogenic erectile dysfunction, meeting the inclusion criteria for the study. Research tools included couples' demographic information, face-to-face interviews, and the International Index of Erectile Function (IIEF). The treatment was based on couple’s therapy. In the initial session, a comprehensive assessment of the couples' condition was conducted, and research instruments were completed. Additionally, during this session, the formation of psychogenic erectile dysfunction and the lack of successful foreplay were discussed. In subsequent sessions, desensitization, instruction on foreplay, and intercourse were addressed. Treatment success was defined as the ability to achieve complete vaginal penetration. Data was analyzed using SPSS 16 software. Results: All 66 couples continued the treatment until they achieved successful vaginal penetration. All International Index of Erectile Function (IIEF) domains improved significantly after couple-based behavioral therapy in men with psychogenic erectile dysfunction in unconsummated marriages (all p < .001; large effect sizes for most domains). No significant associations were found between educational level, place of residence, engagement duration, or marriage duration and post-treatment scores (all p > 0.05). Male age correlated negatively with overall ED (r = −.314, P = .001), erectile function (r = −.361, P = .003), intercourse satisfaction (r = −.365, P = .003), and overall satisfaction (r = −.266, P = .031). Similar negative associations were observed for female age with overall ED (r = −.371, P = .002), erectile function (r = −.354, P = .004), intercourse satisfaction (r = −.344, P = .005), and overall satisfaction (r = −.246, P = .047). Conclusion: Psychogenic erectile dysfunction in unconsummated marriage can be addressed through couple-based therapy.